O papel das cidades na descentralização de políticas nacionais de ciência, tecnologia e inovação - Rosa, Newton Braga (Universidade do Vale do Rio dos Sinos, 2016)
This thesis discusses decentralization of national public policies on Science, Technology and Innovation (ST&I) from the federal to the city government. Governments around the world have been supporting companies and innovation systems because of their relevance to economic viability and national sustainable development. However, despite the increasing political, social and economic relevance of cities worldwide, their role has been underestimated in national ST&I policies. In this context, this study considers how municipal decentralization of national ST&I policies enhances capillarity, efficiency and the strengthening of regional systems of innovation. The study offers empirical evidence of intergovernmental relationships of decentralization through the case studies of two Brazilian cities: Porto Alegre and São Leopoldo, which were selected because of their comparatively good results in promoting companies and systems of innovation in comparison to other Brazilian cities. The main conclusions of the study are: (a) federal government public policy promotion in ST&I remains crucial to the development of entrepreneurial technologically-based systems; (b) municipalities are capable of mobilizing resources, structuring incentive mechanisms, articulating actors, and organizing governance systems; (c) decentralization via municipalities can improve capillarity and effectiveness, strengthening regional innovation systems and consequently complementing national ST&I policies; (d) increased political and economic power of city governments can promote improvements in federal policies of ST&I.
Keywords: Economia regional; Cidades e municípios; Economia do conhecimento; Gestão políticas públicas; Descentralização federativa; Ciência; Tecnologia e inovação; Regional economy; Knowledge economy; Science and technology management; Public policies; Federative decentralization; Technology based ecosystems; ACCNPQ::Ciências Sociais Aplicadas::Administração